PREVALENCE AND IMPACT OF WORKPLACE VIOLENCE AMONG NURSES IN TERTIARY CARE HOSPITALS - AMIN, R; SHAH, S; NAWAZ, N; ALTAF, M; SHEHZADI, A (Biological and Clinical Sciences Research Journal, 2024)
Workplace violence is a significant issue among nurses, particularly in tertiary care hospitals, impacting their well-being and job performance. Understanding the prevalence and types of violence can help develop effective strategies to mitigate these incidents. Objective: To investigate the prevalence, types, frequency, and impact of workplace violence among nurses in tertiary care hospitals in Lahore. Methods: This descriptive cross-sectional study was conducted in various tertiary care hospitals in Lahore over a six-month period following approval. The study population comprised registered nurses, aged 18-65, employed in these hospitals for over a year. A sample size of 108 nurses was calculated using Salvia’s formula, with convenient sampling employed for selection. Data were collected using a self-administered structured questionnaire distributed via Google Forms. The questionnaire covered demographics, experiences of violence, perception of safety measures, coping strategies, and suggestions for improvement. Descriptive statistics were calculated, including frequencies, percentages, means, and standard deviations. Comparisons were made using the independent t-test and chi-square test, with a p-value <0.05 considered significant. Results: Verbal abuse was the most prevalent type of violence, experienced by 62.96% of respondents. Other forms of violence included discrimination (11.11%), physical assault (4.63%), bullying (4.63%), and sexual harassment (1.85%). In terms of frequency, 42.59% of nurses experienced violence rarely, 32.41% frequently, and 25.00% occasionally. The impact of workplace violence included increased stress levels (46.30%), negative impacts on mental health (24.07%), reduced work productivity (16.67%), decreased job satisfaction (11.11%), and physical injuries (1.85%). Conclusion: The study highlights the high prevalence and significant impact of workplace violence on nurses in tertiary care hospitals in Lahore. Verbal abuse was the most common form, with substantial proportions of nurses experiencing frequent violence. These findings underscore the urgent need for targeted interventions to mitigate workplace violence and support affected healthcare workers.